Peralihan Sucker Rod Pump (SRP) ke Electrical Submersible Pump (ESP) pasca Workover Sebagai Upaya Optimalisasi Produksi Sumur “E-030” - Evi Maulia Nilawati; Deny Fatrianto Edyzoh Eko Widodo; M. Nur Mukmin; Fatma; Aprilliano Alfa Kumarsela; Cindy Pebriana; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Optimizing artificial lift systems according to well conditions is essential to achieve the desired production rate. Continuous production often leads to declining flow rates and reservoir pressure, causing incomplete fluid recovery. Water injection helps maintain pressure, while workover operations enhance production rates. This study optimizes well